EXPANDING THE SCOPE OF PSYCHOLOGICAL OPERATIONS IN THE GUERILLA WARFARE CONTEXT - M. K. Nomuratova (Journals Park Publishing, 2024)
This article explores the significance of the moral factor in maintaining a high level of combat spirit in the armed forces.
Keywords: New Uzbekistan, Armed Forces, combat readiness, moral potential, moral factor, Jaloliddin Manguberdi, Amir Temur, material and spiritual factors.